Comparison Of Energy And Protein Intake Between Obese And Normal-Nutrition Children - Idris Idris; Djunaedi Djunaedi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Childhood obesity is a nutritional problem that can increase the risk of metabolic disorders and other health problems. Energy and protein intake are important components that influence nutritional status and growth. Differences in dietary intake between children with obesity and children with normal nutritional status need to be identified as a basis for appropriate nutritional intervention. This study aimed to compare energy and protein intake between obese children and children with normal nutritional status. This quantitative study used a comparative cross-sectional design. The sample consisted of 84 children , consisting of 42 obese children and 42 children with normal nutritional status. Dietary intake was assessed using a food recall questionnaire, while nutritional status was determined based on body mass index-for-age according to applicable growth standards. Data were analyzed using an independent t -test or Mann-Whitney test according to data distribution. The mean energy intake among obese children was 2,145.6 kcal/day, while children with normal nutritional status had a mean intake of 1,782.4 kcal/day. The mean protein intake was 78.5 g/day among obese children and 61.7 g/day among children with normal nutritional status. Statistical analysis showed significant differences in energy intake (p=0.002) and protein intake (p=0.011) between the two groups. Energy and protein intake was significantly higher among obese children than among children with normal nutritional status. Nutritional education and monitoring of dietary intake are important components of obesity prevention and management in children.